Penggunaan Sirs Dalam Rumah Sakit - Lusiana Simanjorang; Rield Rivaldo Benedictus Simbolon (Yayasan Literasi Sains Indonesia, 2023)
A medical record is a document or record containing facts related to the patient's condition, disease history, and past treatment filled in by certain health workers who provide health services to the patient. In general, the system used in hospitals is referred to as SIRS or Hospital Information System. The method used is literature review, where this research is carried out with a data set technique to review books, literature search, notes and reports related to research. Medical record data is used as material for health statistics. Hospital information systems include all public and special hospitals whether they are managed publicly or privately as stipulated in Law of the Republic of Indonesia Number 44 of 2009 concerning Hospitals and Regulation of the Minister of Health No. 82 of 2013 concerning Hospital Management Information System, where article 1 paragraph 6 says that the function of SIRS is to improve efficiency, effectiveness, professionalism, performance, and access to services. Outpatient medical record information systems can facilitate the exchange of outpatient medical records quickly and precisely so that they can be relied upon to provide more complete and fast administration without reducing the accuracy of the information made